2017
DOI: 10.1016/j.polymer.2017.01.055
|View full text |Cite
|
Sign up to set email alerts
|

One-step enzymatic synthesis of poly(p-dioxanone-co-butylene-co-succinate) copolyesters with well-defined structure and enhanced degradability

Abstract: One-step enzymatic synthesis of poly(p-dioxanone-co-butylene-co-succinate) copolyesters with well-defined structure and enhanced degradability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…90 Aerward, a series of monomers have been utilized in this tandem enzymatic polymerization (Fig. 6), e.g., diethyl succinate, 1,4-butanediol and p-dioxanone, 91 L-lactide (LLA) with diesters and diols, 92 u-pentadecalactone (PDL) with diethyl carbonate (DEC), and 1,4-butanediol, 93 lactone with disuldecontaining diester and diol. 94 Among this synthesized polyester, a new biodegradable terpolymerization poly(amine-coesters) formed synthesized by Jiang et al through combined ring-opening and condensation copolymerization of the lactone with dialkyl diester and amino-substituted diols monomers particularly noteworthy.…”
Section: Combination Of Ring-opening Polymerization and Polycondensationmentioning
confidence: 99%
“…90 Aerward, a series of monomers have been utilized in this tandem enzymatic polymerization (Fig. 6), e.g., diethyl succinate, 1,4-butanediol and p-dioxanone, 91 L-lactide (LLA) with diesters and diols, 92 u-pentadecalactone (PDL) with diethyl carbonate (DEC), and 1,4-butanediol, 93 lactone with disuldecontaining diester and diol. 94 Among this synthesized polyester, a new biodegradable terpolymerization poly(amine-coesters) formed synthesized by Jiang et al through combined ring-opening and condensation copolymerization of the lactone with dialkyl diester and amino-substituted diols monomers particularly noteworthy.…”
Section: Combination Of Ring-opening Polymerization and Polycondensationmentioning
confidence: 99%
“…Benefiting from the coexistence of ester and ether bonds in the repeating units, poly( p ‐dioxanone) (PPDO) produced by ring‐opening polymerization (ROP) of p ‐dioxanone (PDO) has attracted much attention in the fields of bioengineering and environmental materials 1–5 . Compared to the conventional aliphatic polyesters that comprise sole ester units, PPDO displays a glass transition temperature ( T g ) of −10 °C and a melting point ( T m ) at 110 °C and shows superior performances (hydrophilicity, degradability and flexibility) 6–8 . For example, PPDO can completely degrade in human body within a period of 180 days that is similar to polyglycolide (PGA) but quite faster than polylactide (PLA), thus render PPDO satisfactory for many biomedical applications 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Its polymerization efficiency was strongly dependent on the purity of the monomer and the activity of the catalysts. [33][34][35] Interestingly, PpDO showed the thermal induced depolymerization to monomer with a yield of more than 90%. 31 3-Methyl-1, 4-dioxan-2-one (MDO) is a homologue of PDO.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the ROP of pDO needs relatively challenging conditions. Its polymerization efficiency was strongly dependent on the purity of the monomer and the activity of the catalysts 33–35 . Interestingly, PpDO showed the thermal induced depolymerization to monomer with a yield of more than 90% 31 .…”
Section: Introductionmentioning
confidence: 99%